1994
DOI: 10.1111/j.1559-1816.1994.tb00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Personality, and Burnout in Nurses

Abstract: This study sought to find evidence for: (a) a relationship between increased levels of work‐related social support and decreased burnout, (b) a relationship between personality traits and burnout, and (c) a significant interaction of social support and extraversion in relation to burnout. Seventy‐six staff nurses and their supervisors at a private medical hospital participated as subjects. Two subscales of the Work Environment Scale measured social support. Personality was measured using an instrument known as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
3
8

Year Published

1995
1995
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 29 publications
3
67
3
8
Order By: Relevance
“…The other personality traits, namely extraversion, neuroticism, openness to experience, and agreeableness, as well as resilience did not appear to be significant predictors of emotional exhaustion in this study. This is in contrast with the results of previous research where it was found that emotional exhaustion is predicted by neuroticism Kokkinos 2007;Jensen 2008), agreeableness (Piedmont 1993;Zeng and Chi 2007), and extraversion (Eastburg et al 1994;Francis et al 2004). Carvalho et al (2006) found that individuals with higher levels of resilience appear to be less emotionally exhausted than individuals with lower levels of resilience.…”
Section: Discussioncontrasting
confidence: 99%
“…The other personality traits, namely extraversion, neuroticism, openness to experience, and agreeableness, as well as resilience did not appear to be significant predictors of emotional exhaustion in this study. This is in contrast with the results of previous research where it was found that emotional exhaustion is predicted by neuroticism Kokkinos 2007;Jensen 2008), agreeableness (Piedmont 1993;Zeng and Chi 2007), and extraversion (Eastburg et al 1994;Francis et al 2004). Carvalho et al (2006) found that individuals with higher levels of resilience appear to be less emotionally exhausted than individuals with lower levels of resilience.…”
Section: Discussioncontrasting
confidence: 99%
“…Konkretno, Neuroticizam je u pozitivnoj vezi (Buhler & Land, 2003;Hills & Norvell, 1991), dok je Ekstraverzija negativno povezana sa sve tri dimenzije izgaranja (Bakker et al, 2006;Lakin et al, 2007). Neuroticizam se tako može shvatiti kao faktor rizika za razvijanje sindroma izgaranja, dok se Ekstraverzija može shvatiti kao protektivni faktor ličnosti (Eastburg, Williamson, Gorsuch, & Ridley, 1994;Francis, Louden, & Rutledge, 2004;Michielsen et al, 2004;Piedmont, 1993;Van Heck, 1997;Zellars et al, 2000).…”
Section: Uvodunclassified
“…Maintaining good relationships and understanding one's colleagues not only helps teams to achieve company objectives, but according to Eastburg et al (1994) and Jackson et al (1986), can even help reduce burnout among employees through the provision of mutual support. Kirmeyer and Koughterty (1998) show that positive perceptions of workplace relationships lead to reduced work-related stress, increased job satisfaction and improved employee performance.…”
Section: Workgroup Relationshipsmentioning
confidence: 99%